Anesthetic concerns and airway management of a 12-year-old child born with craniofacial cleft: A case report - -, Amrita; Kakkar, Mahak (Indian Journal of Case Reports, 2020)
Children born with craniofacial anomalies are usually associated with syndromes such as Treacher Collins, Pierre Robin, Klippel–Feil, craniosynostosis, and its related disorders. These children present with difficult challenges for the anesthesiologist, one being the difficult mask ventilation and intubation. With the recent advances in modern craniofacial surgeries, these facial defects can be corrected to a large extent and thus, a person can lead a normal life. It is important to understand the development and characteristics of the more common anomalies and the challenges associated with them so that we can plan safe anesthesia for these patients. Here, we describe the successful anesthetic management of a 12-year-old child with left Tessier type 12 naso-orbital cleft with a cleft lip and high arched palate. The child was posted for corrective surgery of the facial cleft.